Assembly Automation and Product Design - Boothroyd Geoffrey (Taylor & Francis, 2005)
The design for assembly (DFA) method has become a widely used way for companies to introduce competitive designs at reduced costs. This text places the consideration and application of automatic assembly in the context of DFA, addressing product design for both automated and manual assembly processes. The author enumerates the components, processes, performance, and comparative economics of several types of automatic assembly systems. To this end, the book includes specific information on equipment such as transfer devices, parts feeders, feed tracks, placing mechanisms, and robots. This is an ideal reference and guide for manufacturing, product design, mechanical, and industrial engineers.